A closed loop for municipal organic solid waste by lactic acid fermentation. (January 2015) - Probst, Maraike; Walde, Janette; Pümpel, Thomas; Wagner, Andreas Otto; Insam, Heribert
Highlights: Efficient lactic acid production from unsterilized municipal organic solid waste. Fermentation at pH 5 or uncontrolled pH at 37 °C was highly productive. Selective enrichment of Lactobacilli during the fermentation process. Lactobacillus acidophilus was the main producer of lactic acid. Development of a momentum resulted in community shift after several days. Abstract: In order to investigate the feasibility of producing lactic acid from municipal organic solid waste different pH values (4–7) and temperatures (37 °C and 55 °C) were tested. For the evaluation of fermentation conditions the chemical, physical, and microbial characters were monitored over a period of 7 days. Quantitative real time PCR, PCR–DGGE, and next generation sequencing of a 16S rRNA gene library were applied to identify the key players of the lactic acid production and their association. Lactobacillus acidophilus and its closest relatives were found to be efficient lactic acid producers (>300 mM) under most suitable fermentation conditions tested in this study: 37 °C with either uncontrolled pH or at a pH of 5. These data provide the first step in the realization of the idea "reuse, reduce, and recycle" of municipal organic solid waste.